The Meaning of Qatal - Grasso, Kevin (Journal for semitics, 2021)
This study proposes a novel semantics for the Biblical Hebrew qatal form that includes both perfective and perfect/anterior meanings. I begin by evaluating other theories of qatal and give six criteria with which they might be evaluated, showing past analyses to be inadequate. These criteria are given as an external check on what makes a satisfactory analysis more generally, and though we can learn from past contributions, they ultimately fall short in one of these six areas. In contrast, I show that my theory meets these six criteria for what makes an adequate theory. The single meaning that I give for the qatal form is labelled a "perfect," which I define as an aspectual form that refers to a temporal interval in which either a state holds with a possible preceding event or an event takes place that potentially precedes a state. This is qatal’s particular contribution to the context, though it may have different interpretations as it interacts with various verbal predicates and syntactic and discourse contexts. With this meaning, I account for all the temporal uses of qatal as well as the more difficult optative/precative and counterfactual interpretations. While qatal’s varied uses are recognised and explained, we are able to hold to a single meaning for the form, which is the simplest explanation possible, and this meaning is shown to be typologically and historically plausible.